Long-Term Clinical Outcomes and Parental Satisfaction After Dextranomer/Hyaluronic Acid (Dx/HA) Injection for Primary Vesicoureteral Reflux - Lightfoot, Michelle; Bilgutay, Aylin N.; Tollin, Noah; Eisenberg, Scott; Weiser, Jake; Bryan, Leah; Smith, Edwin; Elmore, James; Scherz, Hal; Kirsch, Andrew J. (Frontiers in Pediatrics, 2019)
Purpose: Endoscopic dextranomer/hyaluronic acid (Dx/HA) injection is a common treatment for vesicoureteral reflux (VUR) with excellent reported short-term clinical success rates. Long-term outcomes are less well defined. We assessed long-term outcomes and parental satisfaction after Dx/HA injection for primary VUR with >5-year follow-up. Materials and Methods: Families of all patients who underwent Dx/HA injection for primary VUR at our institution between 2008 and 2012 were contacted for telephone interview. Data collected by phone included parental satisfaction and presence and severity of UTIs preoperatively and postoperatively. Patient demographics, radiographic VUR data, need for secondary surgery, and surgical indications were obtained through chart review. Results: 575 patients underwent Dx/HA injection for primary VUR between 2008 and 2012. Ninety-nine (17.2%) of these patients' parents were successfully contacted and interviewed. Median follow-up time from surgery to survey was 8.4 (IQR 6.8-9.6) years. Secondary surgery was performed in 13/99 (13.1%), most commonly repeat Dx/HA injection. Seven patients (7.1%) underwent secondary Dx/HA injection for persistent VUR without UTIs at a median of 0.35 (IQR 0.33-0.77) years postoperatively. Five patients (5.1%) underwent Dx/HA injection (n=3) or ureteral reimplantation (n=2) for VUR with febrile UTIs (fUTIs) at a median of 2.2 (IQR 1.3-5.1) years. One patient had ureteral reimplantation for symptomatic obstruction 2.8 years after initial surgery. Only 3/99 (3.0%) required open or laparoscopic surgery after Dx/HA injection. Eighty-three families (84.7%) reported ≥1 fUTIs preoperatively. Of these, only 9/83 (10.8%) reported fUTIs postoperatively, for an overall clinical success rate of 89.2%. Clinical success was 93.1% in patients whose preoperative fUTIs were treated outpatient and 80.0% in those hospitalized at least once for fUTI treatment preoperatively. Ninety-four percent of parents were highly satisfied, 2.4% partially satisfied, and 3.5% dissatisfied. Conclusions: Endoscopic injection with Dx/HA for primary VUR appears to have good long-term clinical success rates and high parental satisfaction, mirroring our previously reported short-term results. Postoperative ureteral obstruction is rare but may occur years postoperatively, justifying initial sonographic surveillance and repeat imaging in symptomatic patients.